URBANIZATION PROCESSES AND ITS SPECIFICS IN LATGALE - Matisovs, Ivars (Via Latgalica, 2010)
Urbanization is an important demo-geographical process and a complex social phenomenon under impact of which changes are made not only to the global, regional or national settlement systems, but all socio-economic processes are also substantially transformed. Changes caused by urbanization have an impact on traditional way of life, cultural particularity, community and individual psychology and other aspects of spiritual life, therefore expressions and regularities of this process might be of interest not only for demographers, geographers and economists, but also for representatives of the field of humanities.Paper presents the progress of urbanization processes in Latgale, by covering the period from establishment of the first urban-type settlements in the Eastern Latvia until today, when under impact of the depopulation processes number of inhabitants in all cities of the region decreases dramatically. Particular attention is paid to the course of formation and evolution of the Latgale urban network, successively looking at characteristics of the course of urbanization process during all major stages of the historical process.Towns and cities constitute the basis for the Latvian population system, characterized by historically formed relatively dense urban network. Like elsewhere in the country, also in modern Latgale towns and cities are distributed evenly throughout the region area, but historically it has not always been so. Urban spatial and landscape model in Latgale has been developed within the long historical process of gradual accumulation of changes in the landscape space; however the balance of this process is destroyed by sudden transformations of political, economic and socio-cultural conditions the region and its people have had to survive in more than one occasion.The article particularly deals with characteristics of the urbanization processes during post-Soviet period, outlines the present urban development trends in Latgale, and highlights major urban demo-geographical problems, among which the emphasis has to be placed on the rapid depopulation, an ageing population and the deepening of territorial inequalities, also intra-regionally.Structural economical changes and increasing mobility of population during the post- Soviet period have changed the urban development perspective. Activities based on new knowledge are concentrated in large agglomerations, while individual regions, including Latgale, with less competitive urban centers are noticeably lagging behind in their development.Therefore, exactly in these areas and localities it is necessary to strengthen the urban functions to impede also interregional migration of population, since it substantially restricts the functionality of the most remote and underdeveloped areas and hinders provision of services to population at an appropriate level. This is even more important since implementation of the cohesion principles has been proclaimed to be one of the cornerstones of the European Union regional policy.Unfortunately, at least for the time being situation in urban areas of Latgale is far from encouraging - negative net migration and negative natural growth factor, persistently high level of unemployment is observed there, social exclusion and apathy prevailing. Admittedly, in recent years urban development in Latgale represents also several positive trends. Urban environmental quality has improved significantly, which is generally associated with transition to environmentally more friendly fuels and implementation of various environmental projects, based on funding from the EU budget, such as municipal waste management, improving of water supply and sewerage systems.Encouragingly, facilities of regional higher education institutions improve, and the capacity of scientific work increases, important interdisciplinary research has been launched. In the nearest future significant educational and scientific infrastructure improvement projects at the University of Daugavpils and Rezekne Higher Education Institution are planned to be made, which will certainly increase competitiveness of the Latgale region in the science and technology area.Article is based on review of comprehensive scientific literature and analysis of available statistical information. The author does not claim to provide all-inclusive and in-depth analysis of the urbanization processes in Latgale, since this task would be performed in course of further studies, but summarizes the results obtained at an early stage of research of urban areas and population demo-geographical development, as well as of the quality of urban environment.